1980
DOI: 10.1288/00005537-198007000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Acute epiglottitis in adults: Experience with fifteen cases

Abstract: Fifteen adults with acute epiglottitis are discussed. Three required tracheostomy because of delayed diagnosis. There were no deaths. Epiglottitis occurs more often in adults than is generally recognized. The early symptoms of epiglottitis in adults are sore throat and dysphagia. Any patient with acute, painful dysphagia should have indirect laryngoscopy to rule out epiglottitis. Throat and blood cultures were obtained from 14 of our cases. Cultures from only two patients were positive for Hemophilus influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 9 publications
1
37
0
1
Order By: Relevance
“…Respiratory distress is a less common feature of the disease in adults compared with paediatric AE, being documented in 25-69% of adults (weighted mean 31%). 1.4,6.7,1 l, 13,16,19,20 Sore throat was present in all of our patients whereas respiratory distress was limited to less than one-third. Oropharyngeal examination with a tongue blade and light appears to be well tolerated in adults with AE and does not induce respiratory distress, despite the commonly expressed concern that sudden airway obstruction may occur as a result of such examination.…”
Section: Discussionmentioning
confidence: 60%
“…Respiratory distress is a less common feature of the disease in adults compared with paediatric AE, being documented in 25-69% of adults (weighted mean 31%). 1.4,6.7,1 l, 13,16,19,20 Sore throat was present in all of our patients whereas respiratory distress was limited to less than one-third. Oropharyngeal examination with a tongue blade and light appears to be well tolerated in adults with AE and does not induce respiratory distress, despite the commonly expressed concern that sudden airway obstruction may occur as a result of such examination.…”
Section: Discussionmentioning
confidence: 60%
“…~'~ The condition in adults is most commonly due to H. influenzae, but may result from Streptococcus pneumuniae, Group A Streptococcus, Group F. Streptococcus, Staphylococcus aureus, Staphylococcus pyogenes, Streptococcus viridans, ~6-20 or Fusobacterium necrophomm. ~3 Two cases of cpiglottitis thought to be due to Haemophilus parainfluenzae have been reported [23][24][25][26] and Adenovirus and Respiratory Syncytial Virus have been implicated, m Blood cultures are most commonly positive if the infection is due to H. influenzae.Z~ , 27 Three cases of epiglottitis associated with Streptococcus pneumoniae bacteremia and several cases due to Candida albicans have been reported in immunocompromised patients. ~9-3~…”
mentioning
confidence: 99%
“…Chan et al recommended artifi cial airway in Friedman Stage III to IV [3]. However, according to Ossoff et al tracheostomy is indicated in progressive disease [18]. In our study, we only intubated the children as they were showing signs of respiratory distress.…”
Section: Discussionmentioning
confidence: 90%